Peran Perekonomian Dalam Pembangunan Nasional Bagi Ketahanan Bangsa - Farida Husin; Zaliah . (Politeknik Negeri Sriwijaya, 2020)
In era of reform and in the global era Indonesian nation, it is no wonder if many aspects will affect the national defense both in terms of ideology, political, economic, social, and cultural aspects of defense and security. The realization economic resilience is reflected in the nation's economic condition is capable of maintaining a healthy economic stability and dynamic, independent, highly competitive, realize the prosperity of the people are fair and equitable.Economic development is directed on the stability of economic resilience through a healthy business climate and utilization of science and technology, availability of goods and services, maintenance of environmental functions, and improve competitiveness within the global economy.